Phonological Processing Difficulties in Indonesian Dyslexic Children: A Parental Observation in the Orangtua Berbagi Community - Muhammad Aziz Fitratama (Universitas Sebelas Maret, 2025)
This study investigates phonological deficits in children with dyslexia within the Orangtua Berbagi community, emphasizing the impact on language comprehension and reading skills. Utilizing a psycholinguistic perspective, the research collects structured parental observations, revealing consistent patterns of phoneme confusion, letter reversals, and decoding difficulties. These deficits significantly hinder children’s ability to accurately process and comprehend written and spoken language. Parents report emotional frustration alongside adaptive strategies such as repetition and visual aids. The findings suggest that early identification through phonological screening and active parental involvement, combined with targeted phonics-based interventions, are crucial to support the language development of dyslexic children. This community-based evidence highlights the need for increased awareness and accessible intervention services tailored to phonological challenges.